RAMIE FIBER-REINFORCED POLYPROPYLENE PELLETS COMPOSITE DEVELOPMENT FOR AUTOMOTIVE INTERIOR APPLICATION - Amos Bastian Sianturi, George
The use of fiber-reinforced polymer (FRP) composites is experiencing rapid development in the industrial world. Unfortunately, the fibers used in FRP systems are currently dominated by synthetic fibres, which are not environmentally friendly, and their availability in Indonesia is small. As a result, natural fibers, which are generally accessible and eco-friendly, start to become more frequently used. In this study, ramie fiber was selected to be the recycled-polypropylene (PP) reinforcement. Ramie fiber was first soaked in NaOH solution at a concentration of 1%, 5%, 10%, 15%, and 17.5% w/w for 24 hours. Then, tensile testing was carried out on native fibers and fibers with chemical treatment by using ASTM D3822 as the reference. Alkalized fibers variant with the highest tensile strength and native fibers are chosen to be combined with recycled PP using the extrusion method. Extruded biocomposite PP pellets reinforced with ramie fiber are processed through injection molding to create specimens for tensile and impact test. Then, using the ASTM D638 standard, tensile testing of ramie fiber-reinforced PP biocomposite specimens was performed. Additionally, impact testing is done using the ASTM D256 standard as a guide. The results showed that alkalization treatment enhanced the fiber's tensile strength and elastic modulus, peaking at 10% w/w NaOH concentration. Alkalization also affects the tensile and impact properties of ramie fiber reinforced PP (PPRF) biocomposites. PPRF with chemical treatment (PPRFT) has an optimal weight fraction that is different from PPRF without chemical treatment (PPRFU). The optimal weight fraction of PPRFT is 10% w/w and the optimal weight fraction of PPRFU is 5% w/w.